Edukasi Preventif Diabetes Melitus : Perubahan Gaya Hidup Dan Pemanfaatan Terapi Herbal Di Kabupaten Banyumas - Rani Prabandari; Theophani Bagas Pradana; Sistia Asfa Fiqrotinnisa; Sevryandi Ega Noer Rachmat Syah; Puput Ma’rifah; Sarjito Hidayat (Jurnal Pengabdian Masyarakat - PIMAS, 2026)
Diabetes mellitus is a major health challenge globally and in Indonesia, where 2021 data reported 19.4 million cases and 236,711 deaths. In Banyumas Regency, cases reached 22,836 by 2024, notably in East Purwokerto and Sokaraja. This community service initiative aimed to enhance public knowledge of diabetes prevention and management through health promotion. Conducted by pharmacist professional students from Universitas Harapan Bangsa in Kranji and Kalikidang Villages, the program followed a three-stage methodology: preparation involving problem analysis, implementation using PowerPoint and discussions, and evaluation. Educational materials covered diabetes types, risk factors, lifestyle modifications, and the use of herbal drinks as low-side-effect alternative treatments. Results indicated successful implementation and high community enthusiasm. Most participants were unemployed women over 30, identified as a high-risk group due to insufficient physical activity. The evaluation emphasized that using simple language and mastering herbal medicine topics are crucial for meeting practical community needs. In conclusion, health promotion effectively increases public understanding as a vital preventive measure to reduce diabetes prevalence in the Purwokerto. This activity demonstrates that structured educational intervention, when tailored to local demographics and practical interests like herbal remedies, can significantly strengthen community-based efforts in managing chronic metabolic diseases and improving overall public health outcomes